Investigation of Antiviral Activities of Nickel and Copper Complexes with Macrocyclic Ligands against Crimean-Congo Hemorrhagic Fever by In Silico Calculations - Erkan, Sultan; Bulut, Niyazi; Karakaş, Duran (My University, 2023)
For the first time, electronic characteristics of potential drug candidates and their inhibitory activities have been linked thanks to this work. Synthesized copper and nickel complexes with trans-N1,N8-bis(2-cyanoethyl)-2,4,4,9,11,11-hexamethyl-1,5,8,12-tetraazacyclotetradecane (tet-bx) ligand, as well as the proposed hypothetical complexes, were properly examined by the appropriate calculation method in atomic and molecular dimensions. The appropriate calculation level was achieved by using the IR spectroscopic data of the tet-bx ligand. The experimental and calculated bond stretching frequencies were compared for synthesized complexes [Ni(tet-bx)](ClO4)2 (1), [Cu(tet-bx)](ClO4)2 (2), [Ni(tet-bx)(NCS)2] (3), and [Ni(tet-bx)(ClO4)Cl] (5). Some bond stretching frequencies of hypothetical complexes [Cu(tet-bx)(NCS)2] (4) and [Cu(tet-bx)(ClO4)Cl] (6) have also been proposed and their molecular structure were determined. To analyze the electronic behavior of the examined complexes at the atomic level, Fukui function indices (nucleophilic f+ and electrophilic f- populations) were determined. Furthermore, antibacterial and antiviral inhibition efficiency of the complexes against Crimean-Congo hemorrhagic fever has been investigated by docking studies
Keywords: Molecular Docking; Fukui function indices; Crimean-Congo